"THE REPRESENTATION OF THE ARCHETYPAL HERO IN ARTHURIAN AND ALPAMYSH EPIC NARRATIVES" - Khakimova Nargiza Khayrilloyevna (International Journal of Literature and Language Studies, 2026)
The hero archetype is a universal figure in world literature, symbolizing courage, leadership, and transformation. Drawing on Jung's (1968) theory of archetypes and Campbell's (2008) concept of the Hero's Journey, this article compares the representation of the archetypal hero in the Arthurian cycle and the Turkic epic Alpamysh. The analysis demonstrates that both Arthur and Alpamysh share common heroic traits, including extraordinary origins, transformative trials, and devotion to their communities. However, each hero reflects the cultural values of his society: Arthur embodies medieval Christian ideals of kingship and chivalry, while Alpamysh represents Turkic values of honor, loyalty, and tribal solidarity (Mirzayev, 1999; Reichl, 2007). The study highlights both the universality and cultural specificity of the hero archetype.